Neuromarketing Awareness and Strategic Implementation among Hotel Employees: An Empirical Analysis in the Udaipur Hospitality Sector - Nisha Tamboli; Dr. Rekha Kumawat (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Neuromarketing has emerged as a transformative tool in understanding and influencing consumer behavior, particularly in experience-centric industries like hospitality. This empirical study explores the level of awareness among hotel employees in Udaipur regarding neuromarketing techniques and examines their strategic application in operational, promotional, and experiential aspects of hotel management. A total of 53 hotel professionals participated in the survey, offering insights into their familiarity with neuromarketing concepts and tools such as fMRI, EEG, eye-tracking, and MEG. One-sample t-tests confirmed statistically significant awareness levels above the minimum threshold across all measured items, rejecting the null hypothesis and establishing that employees hold a substantial understanding of neuromarketing practices. The study further analyzed the deployment of neuromarketing strategies across twelve domains, including website design, sensory engagement, storytelling, pricing, and technological integration. Results show that employees favor techniques like user-friendly digital interfaces, personalized promotions, multisensory environments, and emotional design cues to enhance consumer experience and retention. Bold colors, engaging videos, and loyalty perks were found to be prominent tactics aimed at influencing consumer perception and decision-making. The findings underscore that employees not only possess a significant level of awareness but are actively leveraging neuromarketing insights in their service delivery. This study contributes to neuromarketing literature by bridging the knowledge-practice gap among hospitality professionals and calls for broader institutional training to refine and expand these applications. The research holds implications for hotel administrators, training bodies, and marketers aiming to enhance guest experiences through neuroscience-backed strategies.